HUBUNGAN ANTARA CAPAIAN PEMBELAJARAN DASAR-DASAR PENELITIAN DAN STATISTIK DENGAN MUTU SKRIPSI: STUDI ANALISIS DI STKIP MUHAMMADIYAH BOGOR - Arsyad Arsyad (Khazanah Pendidikan, 2019)
ABSTRACTThe main problem in this study is that students often experience difficulties inwriting thesis, thus affecting the accuracy in completing the study. Among theobstacles is that students do not understand the problems to be studied, and arenot accustomed to writing scientific papers, this is seen in the tendency ofstudents who will write a thesis to look for research titles, not looking forproblems to be studied. This study aims to: First, find out the relationshipbetween the achievements of learning basics of research with the quality of thesis.Second, knowing the relationship between the achievement of statistical learningand the quality of the thesis. Third, knowing the relationship between learningachievement of research basics and achievement of statistical learning with thequality of thesis. The research method is a survey with a correlational form, witha population of STKIP Muhammadiyah Bogor students in semester VIII (eight)of 2016/2017 academic year totaling 126 people, with a sample of 40 people. Theconclusion of this study are: First, there is a positive influence between thevariables of learning achievement of research basics (X1) with the quality ofthesis (Y). Second, there is a positive influence between the variables of theachievement of statistical learning (X2) with the quality of the thesis (Y). Third,there is a positive relationship between the variables of learning achievement ofresearch basics (X1) and achievement of statistical learning (X2) with the qualityof thesis (Y).Keywords: learning achievement, research basics, statistics, and thesis quality.